Analisi Usaha Tani Jeruk Siam Gunuang Omeh (JESIGO) Dalam Upaya Meningkatkan Pendapatan Petani di Kecamatan Gunuang Omeh Kabupaten Lima Puluh Kota - ilham fani; Ratna Wilis (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This article was Written to analyze income, efficiency level, and marketing network of Gunuang Omeh Conjoined Orange Farming Business in Gunuang Omeh District, Lima Puluh Kota Regency. This type of research uses descriptive methods with a quantitative approach. The population in this study was 1,346 conjoined orange farmers in Gunuang Omeh District Lima Puluh Kota Regency. Sampling in this study used the Slovin formula so that 93 respondents were obtained by farmers. The result of research relating to the Gunuang Omeh Conjoined Orange Farming Business are as follows: 1)The average income of citrus farmers in the District of Gunuang Omeh is Rp 1,454,679 in one mont. 2) The level of efficiency obtained by farmers from the farming of tangerines in the Subdistrict of Gunuang omeh 1.52, meaning that the business of tangerines is efficient for farmers. 3) the marketing network of the Gunuang Omeh Conjoined Orange Farm Business, the First marketing network (farmer-collector-retailer-consumer) and second marketing nedwork (the farmer-consumer).